2021
DOI: 10.1111/jocn.16073
|View full text |Cite
|
Sign up to set email alerts
|

The Manchester Triage System's performance in clinical risk prioritisation of patients presenting with headache in emergency department: A retrospective observational study

Abstract: Objective Non‐traumatic headache is a frequent reason for visits to the emergency department (ED). We evaluated the performance of the Manchester Triage System (MTS) in prioritising patients presenting to the ED with non‐traumatic headache. Methods In this single‐centre observational retrospective study, we compared the association of MTS priority classification codes with a final diagnosis of a severe neurological condition requiring timely management (ischaemic or haemorrhagic stroke, subarachnoid haemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…First, ophthalmic crises were concentrated on ocular disorders and had fewer considerations than general ED visits, which must take into account systemic manifestations. Second, most general EDs employed a four-or five-level classification system ( [27][28][29], which made triage more challenging for nurses than the three-level triage in our study. Interestingly, although we confirmed that there was strong agreement between nurses and doctors, we discovered that nurses tended to give a "semi-emergency" grade to all patients.…”
Section: Discussionmentioning
confidence: 96%
“…First, ophthalmic crises were concentrated on ocular disorders and had fewer considerations than general ED visits, which must take into account systemic manifestations. Second, most general EDs employed a four-or five-level classification system ( [27][28][29], which made triage more challenging for nurses than the three-level triage in our study. Interestingly, although we confirmed that there was strong agreement between nurses and doctors, we discovered that nurses tended to give a "semi-emergency" grade to all patients.…”
Section: Discussionmentioning
confidence: 96%
“…pathologies, with an overtriage rate ranging from 7.6% to 54%. 10,18 Overtriage leads to problems in the ED management of patient flow, as patients with benign disorders are visited earlier than those with urgent and time-dependent pathology. It results also in a prolonged ED stay and an increased number of unnecessary diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different studies have focused on evaluating the performance of MTS on individual symptom presentations, reporting conflicting results about its ability. While some studies have demonstrated a good ability of MTS to correctly identify and stratify certain symptoms and specific pathologies (e.g., chest pain, headache, and dyspnea), for other symptoms it has revealed a lower ability to prioritize patients with time‐dependent pathologies (e.g., cardiac syncope and pulmonary embolism) 7,8,10–13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies in the literature have attempted to evaluate the accuracy of triage systems, both globally and when comparing time‐dependent pathologies, by studying the correct stratification of patients (Azeredo et al, 2015; Brigo et al, 2022; Zaboli, Ausserhofer, Sibilio, Paulmichl, Toccolini, Losi, et al, 2022). In such studies, the triage priority code was always correlated with the patient's clinical outcome; unfortunately, only a few and limited studies have performed subsequent evaluations about the type of error to understand whether it was depending on a wrong application of the triage system or whether it was a problem present within the triage system itself (Brigo et al, 2022; Zaboli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%